Transforming Human Resources into Human Capital - Zakaria, Sabarudin (Information Management and Business Review, 2011)
Human resource refers to the stock of productive skills and technical knowledge embodied in labor. It is tangible in nature. Many early economic theories refer to it simply as labor, one of the three factors of production, and consider it to be a fungible resource – homogeneous and easily interchangeable. The goal of human resource management is to help an organization to meet strategic goals by attracting, and retaining employees and also to manage them effectively so that they deliver productive outputs. The key word here perhaps is "fit", i.e. a HRM approach seeks to ensure a fit between the management of an organizationâ€™s employees, and the overall strategic direction of the company. Human capital instead, refers to the intangible aspect of human resources. It enhances the value of employees by striking a win-win goal for employers and employees. It focuses on the intrinsic value of each employee, where any expenditure on employees is regarded as an investment rather than an expense. The varying talents and motivations of employees are given cognizance so that incentives and working arrangements can be created to enhance each employee’s contributions to organizational performance. This paper distinguishes human capital from human resources and how human resource may be transformed into human capital.